Profile of medication variations and dose adjustment to diabetes mellitus patients’ response in PKU Muhammadiyah hospital and Panti Rapih hospital period October–December 2014 - Faridah, Imaniar Noor; Perwitasari, Dyah Aryani; Kusumaningsih, Desty; Handayani, Riana Prastiwi (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2018)
Background: Diabetes mellitus patients may have a different response to similar medication. Therefore, individualized treatment and monitoring of the therapy is needed to ensure the patients’ response. Alternative medication or dose adjustment should be considered in order to achieve the therapeutic goal. Objective: The aim of this study was to find out patients’ response to medication variation or dose adjustment. Methods: This study used descriptive design in PKU Muhammadiyah Hospital and Panti Rapih hospital period October-December 2014. Participants are all patients who got pharmacological therapy for treatment of diabetes mellitus type 2, including oral antidiabetics and/ insulin and met the inclusion criteria. The response of therapy was checked 2 times, during check-in and check-out. Results: Analysis of response variation showed that individualized response existed, in which positive response occurred in 10 patients and the other had a negative response. The changes were dose adjustment and medication alteration or medication addition. From 6 patients who needed medication adjusment, 5 patients had a positive response, and others had a negative response. Whereas from 6 patients whose dosage or medication was not changed, 5 of them had a positive response while one had a negative response. Conclusion: Individualized treatment is needed to achieve a therapeutic goal. Individualized treatment can be done through dose adjustment and medication alteration, or medications addition.